Access versus success: Services for students with disabilities in postsecondary education. - Sassu, Kari (Journal of Educational Leadership and Policy Studies, 2018)
Keywords: dept.csp; peer-reviewed; ⛔ No DOI found

Autism and intersectionality: Considerations for school-based practitioners - Sassu, Kari A.; Volkmar, Fred R. (Psychology in the Schools, 2022)
The purpose of this article is to explore the intersectionality of autism and sociocultural factors as well as discuss the complexities associated with appropriate assessment, diagnosis, and intervention. Based on a review of the literature, the authors present a brief history of the emergence of the term autism and highlight factors that have contributed to current concerns about failures to appropriately recognize autism within diverse populations. Referencing extant research as well as professional practice standards, this article examines aspects of autism and intersectionality, and explores some of the associated challenges related to assessment, diagnosis, and intervention. Further, the authors reflect on the critical importance of carefully considering all aspects of a child's identity when engaging in autism assessment and intervention within the school setting. School-based practitioners are provided with guidance for addressing the needs of diverse populations of students with autism.
Keywords: SES; autism; dept.csp; dept.sed; ethnicity; intersectionality; peer-reviewed; race

The Neurospicy Queer Experience: Insights Into the Lived Experiences & Counseling Needs of Transgender and Gender Expansive Adults with ADHD - Gorski, J.; Bonjo, L.; Sassu, Kari; Councilor, KC (Journal of LGBTQ Issues in Counseling, 2026)
Keywords: ADHD; Expansive; Human sexuality; Lived experience; Qualitative research; Queer; Transgender; dept.com; dept.csp; gender affirming care; gender expansive; neurodivergence; neuroqueer; neurospicy

Written emotional expression in schools: Processing psychological and emotional stress through narrative writing. - Sassu, Kari A.; Bray, Melissa A.; Gelbar, Nicholas; Kerzner, Tiffany P. (Promoting mind–body health in schools: Interventions for mental health professionals., 2020)
Keywords: dept.csp

Culturally responsive practice and the role of school administrators - Minkos, Marlena L.; Sassu, Kari A.; Gregory, Jess L.; Patwa, Shamim S.; Theodore, Lea A.; Femc-Bagwell, Michele (Psychology in the Schools, 2017)
In recent years, student populations within public schools in the United States have become increasingly diverse, both culturally and linguistically, and are projected to continue to grow in diversity in the future. Consequently, educators must be prepared to support the needs and education of students with multicultural backgrounds who may differ from them. School administrators play an important role in creating safe, accepting school environments and guiding the education of diverse student populations. However, there is a need for additional guidance for school leaders in cultivating schools that promote equity for all students. Using the National Policy Board for Educational Administration (NPBEA) Professional Standards for Educational Leaders as a guiding framework, this paper provides practical suggestions regarding culturally responsive strategies and practices that school administrators might employ in leading diverse school communities.
Keywords: culturally responsive practice; dept.csp; dept.edl; diversity; educational leadership; peer-reviewed

Psychologically based therapies to improve lung functioning in students with asthma. - Maykel, Cheryl; Bray, Melissa A; Gelbar, Nicholas W; Caterino, Linda C; Avitia, Maria J; Sassu, Kari; Root, Melissa M (International journal of school and educational psychology, 2016)
Asthma is a common, chronic respiratory disease that can be costly to both society and the individual. In addition to increased absenteeism, children with asthma may also be at a greater risk for developing comorbid anxiety and depression. Various complementary psychological treatments have been effective at reducing both asthmatic symptoms and psychological distress. Although the research in the area of mind-body treatments as it pertains specifically to persons with asthma is still developing, this article will describe several promising alternative treatment methods, many of which have already been, or could be easily be applied for use in a school setting. © 2016, © 2016 International School Psychology Association.
Keywords: art therapy; asthma; biofeedback; dept.csp; hypnosis; mind-body; mindfulness; music therapy; relaxation and guided imagery; school-based interventions; written emotional expression; yoga

Do the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability? - Pagirsky, Matthew S.; Koriakin, Taylor A.; Avitia, Maria; Costa, Michael; Marchis, Lavinia; Maykel, Cheryl; Sassu, Kari; Bray, Melissa A.; Pan, Xingyu (Journal of Psychoeducational Assessment, 2017)
A large body of research has documented the relationship between attention-deficit hyperactivity disorder (ADHD) and reading difficulties in children; however, there have been no studies to date that have examined errors made by students with ADHD and reading difficulties. The present study sought to determine whether the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability. The participants in this study were 91 students in the ADHD clinical validity standardization sample of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3), as well as a control group of 63 students selected from the larger standardization sample. Students with ADHD and reading difficulties demonstrated a statistically significant greater amount of errors across tests of academic achievement. Findings from the study are discussed within the context of past research, as well as implications for the field of school psychology and practitioners.
Keywords: achievement; attention-deficit hyperactivity disorder; dept.csp; reading; special education

Biological gender differences in students’ errors on mathematics achievement tests - Stewart, Christie; Root, Melissa M.; Koriakin, Taylor; Choi, Dowon; Luria, Sarah R.; Bray, Melissa A.; Sassu, Kari; Maykel, Cheryl; O’Rourke, Patricia; Courville, Troy (Journal of Psychoeducational Assessment, 2017)
This study investigated developmental gender differences in mathematics achievement, using the child and adolescent portion (ages 6-19 years) of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3). Participants were divided into two age categories: 6 to 11 and 12 to 19. Error categories within the Math Concepts & Applications and Math Computation subtests of the KTEA-3 were factor analyzed and revealed five error factors. Multiple ANOVA of the error factor scores showed that, across both age categories, female and male mean scores were not significantly different across four error factors: math calculation, geometric concepts, basic math concepts, and addition. They were significantly different on the complex math problems error factor, with males performing better at the p ¡ .05 significance level for the 6 to 11 age group and at the p ¡ .001 significance level for the 12 to 19 age group. Implications in light of gender stereotype threat are discussed.
Keywords: KTEA-3; achievement; dept.csp; error analysis; factor analysis; gender; math